Impact of COX2 genotype, ER status and body constitution on risk of early events in different treatment groups of breast cancer patients. Issue 8 (20th March 2014) - Markkula, Andrea; Simonsson, Maria; Rosendahl, Ann H.; Gaber, Alexander; Ingvar, Christian; Rose, Carsten; Jernström, Helena
<x xml:space="preserve">Abstract</x> The COX2 rs5277 (306G>C) polymorphism has been associated with inflammation‐associated cancers. In breast cancer, tumor COX‐2 expression has been associated with increased estrogen levels in estrogen receptor (ER)‐positive and activated Akt‐pathway in ER‐negative tumors. Our study investigated the impact of COX2 genotypes on early breast cancer events and treatment response in relation to tumor ER status and body constitution. In Sweden, between 2002 and 2008, 634 primary breast cancer patients, aged 25–99 years, were included. Disease‐free survival was assessed for 570 rs5277‐genotyped patients. Body measurements and questionnaires were obtained preoperatively. Clinical data, patient‐ and tumor‐characteristics were obtained from questionnaires, patients' charts, population registries and pathology reports. Minor allele(C) frequency was 16.1%. Genotype was not linked to COX‐2 tumor expression. Median follow‐up was 5.1 years. G/G genotype was not associated with early events in patients with ER‐positive tumors, adjusted HR 0.77 (0.46–1.29), but conferred an over 4‐fold increased risk in patients with ER‐negative tumors, adjusted HR 4.41 (1.21–16.02)(pinteraction = 0.015). Chemotherapy‐treated G/G‐carriers with a breast volume ≥850 ml had an increased risk of early events irrespective of ER status, adjusted HR 8.99 (1.14–70.89). Endocrine‐treated C‐allele carriers with ER‐positive tumors and a breast volume ≥850 ml had increased risk of early events, adjusted HR 2.30 (1.12–4.75). COX2 genotype, body constitution and ER status had a combined effect on the risk of early events and treatment response. The high risk for early events in certain subgroups of patients suggests that COX2 genotype in combination with body measurements may identify patients in need of more personalized treatment.